Explaining the role of the event patterns derived from natural and cultural factors in shaping the spatial patterns of vernacular architecture; Case study: Sar Agha Seyyed village - Seyyed Mohammadmahdi Hosseinikia; Parisa Hashempour; Leila Medghalchi; Aida Maleki (مسکن و محیط روستا, 2022)
Iranian vernacular architecture has a wide geographical scope and sustainability principles that need more than ever to be analyzed, reread and criticized scientifically and fairly. A reading that is the basis for improving the processes and methods of preserving these properties, the intervention method, achieving the cultural roots and architectural typology of Iran. As much influenced by natural factors, vernacular architecture also follows mental beliefs, local culture, and individual and social events. Cultural factors form the spirit that governs all spatial patterns of vernacular architecture and the event pattern embodied in them. Bearing this in mind, spatial patterns are influenced by event patterns and event patterns are also influenced by culture and nature, and consequently, vernacular architecture is considered a cultural manifestation. This study is the result of investigating the quality of interaction of cultural aspects and natural context and their impact on events and accordingly the vernacular architecture of Sar Aqa Seyyed village, in Koohrang county of Chaharmahal and Bakhtiari province. The main purpose of this qualitative research is to identify and present a model-based framework for analyzing the vernacular architecture of Sar Aqa Seyyed village to determine the event patterns and spatial patterns shaping it and the relationship between them by investigating the cultural patterns and the natural context of the case study. The research question is how spatial patterns relate to people's beliefs, cultural roots and natural limitations, as well as how they occur in the physical structure of the village. The study was performed by a descriptive-analytical method through field observations, objective studies and analytical sketches as well as in-depth interviews in order to identify the constituent patterns of the target village. The results indicate that the event patterns are objective manifestations of cultural and natural factors that are displayed in the form of spatial patterns.